Marginal gap of three-dimensional printed full-arch frameworks supported by all-on-four and all-on-six implant designs - Leticia Del Rio Silva; Thaís Barbin; Daniele Valente Velôso; Marcelo Ferraz Mesquita; Guilherme Almeida Borges (The Journal of Indian Prosthodontic Society)
Aim: The aim of this study was to evaluate the marginal gap of full-arch frameworks (FAFs) supported by all-on-four and all-on-six implant designs, fabricated using different manufacturing technologies. Settings and Design: This was an in vitro study. Materials and Methods: Fifteen titanium FAFs were fabricated using milling and three-dimensional printing techniques: selective laser melting (SLM) and electron beam melting (EBM) (n = 5/group). The marginal gap between the framework and abutment was measured using a microscope with 1 μm accuracy. Measurements were taken three times by a calibrated examiner (intraclass correlation coefficient of 0.996; P < 0.001) at the buccal and lingual interface between the abutment and the framework. Statistical Analysis Used: A two-way ANOVA was applied to assess the effects of implant design and manufacturing technology (α = 0.05). Results: When comparing implant designs, the all-on-four group (milling [P = 0.002] and SLM [P = 0.001]) exhibited lower marginal gap values than the all-on-six group. No statistically significant difference was observed between the EBM frameworks in both designs. In the all-on-four group, milling resulted in lower marginal gap values than SLM (P = 0.021) and EBM (P = 0.001), while no statistically significant difference was found between the SLM and EBM groups (P = 0.163). For the all-on-six framework design, the milling (P = 0.008) and EBM (P < .001) groups exhibited lower marginal gap values than the SLM group. No statistically significant difference was detected between the milling and EBM groups (P = 0.160). Conclusion: Milled frameworks should be the preferred choice for rehabilitations using the all-on-four implant design. For the all-on-six design, both milled and EBM frameworks may be indicated. The marginal gap values observed for all FAFs designs and manufacturing technologies can be considered clinically acceptable.